Assessment of sublethal and transgenerational effects of spirotetramat, on population growth of cabbage aphid, Brevicoryne brassicae L. (Hemiptera: Aphididae) - Iftikhar, Ayesha; Hafeez, Faisal; Aziz, Muhammad Asif; Hashim, Muhammad; Naeem, Afifa; Yousaf, Hafiz Kamran; Saleem, Muhammad Jawad; Hussain, Sabir; Hafeez, Muhammad; Ali, Qurban; Rehman, Muzammal; Akhtar, Sumreen; et al. (Frontiers in Physiology, 2022)
The cabbage aphid (Brevicoryne brassicae L.) is a devastating pest of cruciferous crops causing economic damage worldwide and notably owing to its increasing resistance to commonly used pesticides. Such resistance prompts the development of integrated pest management (IPM) programs that include novel pesticides being effective against the aphids. Spirotetramat is a novel insecticide used against sap-sucking insect pests, particularly aphids. This study evaluated the toxicity of spirotetramat to adult apterous B. brassicae after 72 hours using the leaf dipping method. According to the toxicity bioassay results, the LC50 value of spirotetramat to B. brassicae was 1.304 mg L-1. However, the sublethal concentrations (LC5 and LC15) and transgenerational effects of this novel insecticide on population growth parameters were estimated using the age-stage, two-sex life table theory method. The sublethal concentrations (LC5; 0.125 mg L-1 and LC15; 0.298 mg L-1,) of spirotetramat reduced the adult longevity and fecundity of the parent generation (F0). These concentrations prolonged the preadult developmental duration while decreasing preadult survival, adult longevity and reproduction of the F1 generation. The adult pre-reproductive period was also extended by spirotetramat treatment groups. Subsequently, the population growth parameters such as the intrinsic rate of increaser, finite rate of increase λ and net reproductive rate R0 of the F1 generation were decreased in spirotetramat treatment groups whereas, the mean generation time T of the F1 generation was not affected when compared to the control. These results indicated the negative effect of sublethal concentrations of spirotetramat on the performance of B. brassicae by reducing its nymphal survival, extending the duration of some immature stages and suppressing the population growth of B. brassicae. Overall, we demonstrated that spirotetramat is a pesticide showing both sublethal activities, and transgenerational effects on cabbage aphid; it may be useful for implementation in IPM programs against this aphid pest.